THE ROLE OF PARENTS ON THE FORMING OF CHILDREN'S CHILDREN IN THE FAMILY: THE THEMATIC HADITH STUDY - Siti Yumnah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
The purpose of this article is to find out and explain the role of parents in the formation of children's morals in the family, as explained in the hadith of the Prophet Muhammad SAW. This study uses a qualitative method to describe the role of parents in the formation of children's morals in the hadith perspective family. In this study, there are two types of data sources used, primary and secondary. Primary data sources are information collected directly from information sources through informants, while secondary data sources in this study provide supporting information. for example, the results of publications related to research. The data collection technique uses various approaches, namely from the literature which includes not only books but also the results of documentation, magazines, newspapers, especially in the verses of the Qur'an and the hadith of the Prophet Muhammad. Furthermore, the data is processed and sorted for analysis, and then conclusions are drawn. In this article explains, there are four ways the role of parents in fostering children's morals according to the hadith of the Prophet which has been described in the discussion above, including, First, Educating away from the haram. second, instilling honesty in children. Third, greet when meeting someone, and Fourth. Say hello when you enter the house say hello when meeting someone, and Fourth. Say hello when you enter the house say hello when meeting someone, and Fourth. Say hello when you enter the house.